UNFORGETTABLE DREAM IN BRENNANÃ¢â¬â¢S POEM - Nugroho, Henriono (Language Circle: Journal of Language and Literature, 2009)
This article concerns with a stylistic analysis on a poem in terms of Systemic Functional Linguistics and Verbal Art Semiotics. The writing uses library research, qualitative data, documentary study, descriptive method and intrinsic-objective approach. The semantic analysis results in both automatized and foregrounded meanings. Then the automatized meaning produces lexical cohesion and in turn, it produces subject matter. Meanwhile, the foregrounded meaning produces the literary meaning and in turn, it creates theme. Finally, the analysis indicates that the subject matter is about a young man in his girlfriendÃ¢â¬â¢s dream, the literary meaning is about the memory of dream and the theme is about the unforgettable dream. Keyword: automatized meaning, foregrounded meaning, subject matter, literary meaning, theme